Informal, formal institutions and credit: complements or substitutes?. Issue 4 (18th February 2019) - Cruz-García, Paula; Peiró-Palomino, Jesús
Abstract: This paper analyses the relationship between informal institutions measured by social trust and the provision of private credit. Research on the trust–finance relationship abounds, although most of it is confined to the micro-level, with far fewer contributions from a wide, cross-country perspective. Considering a sample of 119 economies in the period 1993–2015, results suggest that social trust is an important determinant of private credit, and that its effects are transmitted indirectly via some particular aspects of the quality of economic-judicial institutions. In addition, and contrary to previous findings in related areas, substitutive effects for informal and formal institutions are not found. Therefore, informal institutions can improve the quality of the certain types of formal institutions but they are, per se, unable to replace them in the provision of credit. Accordingly, a solid economic-judicial system becomes essential to guarantee credit transactions.